Unfinished business of living : helping aging parents help themselves - Chapman, Elwood N. (Crisp Pub. Los AltosUS, 1988)
Targets the middle generation who must sandwich their lives between the care of aging parents and that of their own families. Addresses the need for adult children to recognize and adapt to the diminishing capabilities of senior family members. Advocates the need to incorporate support systems, but also discusses interventions by family members with regard to timing, manner, level etc. Shows how caring for/about the elderly benefits both care-giver and care receiver; and discusses strategies for lessening the number of unfinished tasks to be completed when elderly parents die.